Different importance of primary lymphoid organs for Rous sarcoma regression in inbred lines of chickens - Plachý, J; Benda, V; Karakoz, I; Spaténková, Z (Folia biologica, 1984)
Resistance to progressive growth of tumours induced by Rous sarcoma virus is controlled mainly by genes linked to the B complex (the major histocompatibility complex) of the chicken. The effect of thymectomy and bursectomy on this resistance was studied in chickens from highly inbred lines and their F1 hybrids which differ by the genotype at the B complex and by the degree of genetically controlled resistance or susceptibility. The results show that thymectomy has considerable effect on growth of RSV-induced tumours in the CB line genetically resistant to progressive Rous sarcoma growth and little effect in (CB X IC)F1 (also genetically resistant) and (CC X IC)F1 (intermediate responders to RSV) hybrid chickens. Bursectomy influences the expression of this resistance to a lesser extent than thymectomy. The results indicate that resistance to the development of progressively growing tumours is of a complex nature, the individual components of the immune system are more or less important for its expression in different experimental models. Thus genetically defined animal models have become useful tools for studying carcinogenesis.
Keywords: ptačí sarkom; imunita; Immunity; bursa Fabricii; Sarcoma, Avian; Thymus Gland; hlavní histokompatibilní komplex; thymus; genotyp; kur domácí; Animals; Bursa of Fabricius; Genotype; Major Histocompatibility Complex; Chickens; zvířata; Lymphoid Tissue; lymfoidní tkáň